Management of the biodegradable fraction of residual waste by bioreactor landfill. Issue 10 (October 2020) - Di Maria, Francesco; El-Hoz, Mervat
The performances of an integrated system based on mechanical biological treatment and bioreactor landfill with leachate recirculation for managing the mixed municipal solid waste generated in a given Italian district were investigated. In the mechanical biological treatment the municipal solid waste was mechanically sorted into two main streams: a dry and a mechanically sorted organic fraction consisting of 45, 000 tonnes year −1 . After being sorted the mechanically sorted organic fraction was aerobically pretreated before being disposed of in the 450, 000 m 3 bioreactor landfill. Experimental runs showed that an aerobic pretreatment period ranging from 15 to 30 days was able to maximize the methane generated by the mechanically sorted organic fraction once landfilled up to 10 Nm 3 tonne −1 . The aerobic pretreatment leads to a significant volatile solids reduction in the first 30 days, after which the volatile solids concentration remained quite constant. Similarly the potential dynamic respirometer index was significantly reduced in the first 15 days of the aerobic pretreatment decreasing from about 5, 000 to about 3, 500 mgO2 kgVS −1 h −1 . The whole amount of electrical energy producible by the landfill ranged from 18.5 kWh tonne −1 to 21 kWh tonne −1, depending on the strategies adopted for the activation in bioreactor mode of each landfill cell by the leachate recirculation.